Developing Vocabulary Through Media Android’s Application for a Child in 2013 Curriculum - A Alfiansyah; Darin Fouryza; Yeni Silviani (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
This article aims to analyze how much influence the use of android applications to increase children vocabulary. Vocabulary was a part of children language development, that must be stimulated from an early age. Vocabulary played an important role for children, because by mastering the vocabulary can make it easier for children to communicate with their environment. Through android applications, children were easy to get the packed knowledge as attractive as possible using images and motion animations accompanied by audio. The powerful appeared of android applications for children is not separated from the characteristics of the media that has several advantages compared to the print media and hearing media, so children liked it very much. Android applications have a significant impact on the children vocabulary, if learning on the Indonesia language in curriculum 2013 used that media,accordingly the impact was good.